Freedom, the Media, and War: an Investigation on Interactions - Steltemeier, Andra (Žurnalistikos tyrimai, 2015)
This paper is set to analyze interdependencies of freedom, media, and war. In order to show freedom’s impacts on the latter, first historical and current concepts are discussed. To cope with recent developments in both war and media, a categorization of old and new wars is then depicted in order to sketch the major differences. Terrorism as a new appearance of war is examined in more detail, as it provides a comprehensive example of how all subcomponents of the investigation – freedom, media and war – interact. The media with their special role in regard to freedom, war, and state, are more specified in order to follow the logical scope of the paper. It is shown how the three stated elements reciprocally depend on each other. Lastly, the possible solutions for inhibiting negative interactions are presented. Due to its largest lever, the focus is hereby placed on the media.